Assessing the Relationship Between Work–Family Conflict and Smoking - Nelson, Candace C. (American Public Health Association, 2012)
Objectives. We examined the relationship between smoking and work–family conflict among a sample of New England long-term-care facility workers. Methods. To collect data, we conducted in-person, structured interviews with workers in 4 extended-care facilities. Results. There was a strong association between smoking likelihood and work–family conflict. Workers who experienced both stress at home from work issues (i.e., work-to-home conflict) and stress at work from personal issues (i.e., home-to-work conflict) had 3.1 times higher odds of smoking than those who did not experience these types of conflict. Workers who experienced home-to-work conflict had an odds of 2.3 compared with those who did not experience this type of conflict, and workers who experienced work-to-home conflict had an odds of 1.6 compared with workers who did not experience this type of conflict. Conclusions. The results of this study indicate that there is a robust relationship between work–family conflict and smoking, but that this relationship is dependent upon the total amount of conflict experienced and the direction of the conflict.